Factors affecting the adoption of CBDCs for financial transactions - Jindal, Kiran; Khera, Kavya (Ushus Journal of Business Management, 2025)
One important development in payments and finance is the emergence of central bank digital currencies, or CBDCs. India is at a turning point in its contemplation of implementing CBDCs because of its quickly expanding digital economy. Through primary research and data analysis, this study investigates the factors impacting the use of CBDCs for financial transactions in India. A mixed-approaches research methodology is used in this work, integrating quantitative and qualitative data collection methods. Aspects of CBDC adoption such as awareness, attitudes, perceived benefits, and concerns are all included in the survey questionnaire. The findings focus on privacy issues and lack of awareness in CBDC adoption tactics.